Wnt signaling and Dupuytren's disease. - Dolmans, G; Werker, P; Hennies, H; Furniss, D; Festen, E; Franke, L; Becker, K; van der Vlies, P; Wolffenbuttel, B; Tinschert, S; Toliat, MR; Nothnagel, M; et al. (2011)
BACKGROUND: Dupuytren's disease is a benign fibromatosis of the hands and fingers that leads to flexion contractures. We hypothesized that multiple genetic and environmental factors influence susceptibility to this disease and sought to identify susceptibility genes to better understand its pathogenesis. METHODS: We conducted a genomewide association study of 960 Dutch persons with Dupuytren's disease and 3117 controls (the discovery set) to test for association between the disease and genetic markers. We tested the 35 single-nucleotide polymorphisms (SNPs) most strongly associated with Dupuytren's disease (P<1×10(-4)) in the discovery set in three additional, independent case series comprising a total of 1365 affected persons and 8445 controls from Germany, the United Kingdom, and The Netherlands. RESULTS: Initially, we observed a significant genomewide association between Dupuytren's disease and 8 SNPs at three loci. Tests of replication and joint analysis of all data from 2325 patients with Dupuytren's disease and 11,562 controls yielded an association with 11 SNPs from nine different loci (P<5.0×10(-8)). Six of these loci contain genes known to be involved in the Wnt-signaling pathway: WNT4 (rs7524102) (P=2.8×10(-9); odds ratio, 1.28), SFRP4 (rs16879765) (P=5.6×10(-39); odds ratio, 1.98), WNT2 (rs4730775) (P=3.0×10(-8); odds ratio, 0.83), RSPO2 (rs611744) (P=7.9×10(-15); odds ratio, 0.75), SULF1 (rs2912522) (P=2.0×10(-13); odds ratio, 0.72), and WNT7B (rs6519955) (P=3.2×10(-33); odds ratio, 1.54). CONCLUSIONS: This study implicates nine different loci involved in genetic susceptibility to Dupuytren's disease. The fact that six of these nine loci harbor genes encoding proteins in the Wnt-signaling pathway suggests that aberrations in this pathway are key to the process of fibromatosis in Dupuytren's disease.